Forced to Freedom? Empirical relations between aid and economic freedom - Franz Kronthaler; Tobias Knedlik (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2007)
The paper explores the relationships between economic freedom on the one side and development aid and IMF credit as approximation for conditional aid on the other side. After a short review of current literature the paper develops a simple panel regression model to evaluate the relationships. In contrast to previous research, our results allow the rejection of the hypothesis that IMF credit increases economic freedom and that development aid is not contributing to economic freedom. It could not be shown that countries can be forced to economic freedom by aid conditions. The paper discusses explanations of the empirical findings.
Keywords: P10; F35; O19; 330; Aid receiving countries; economic freedom; development aid; IMF credit